1979
DOI: 10.1111/j.1365-2044.1979.tb06332.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature and incidence of complications of peripheral arterial puncture

Abstract: Follow-up of the sites of 839 peripheral arterial punctures has confirmed the technique as safe and free from major sequelae. Minor complications, mainly bruising and tenderness, occurred at 39% of sites; this incidence is much less than that previously reported following short-term arterial cannulation. At only 2% of sites was there any significant pain or tenderness. There was a small incidence of pulse diminution particularly at the radial site but no case of arterial occlusion. The use of a smaller needle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…Yet, arterial puncture, most often of the radial artery, is a safe and simple procedure. With the exception of local pain, bruising and haematoma, clinically significant complications are rare [ 23 , 24 ]. Local pain may be decreased by local anaesthetic infiltration or the application of ice prior to the puncture [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, arterial puncture, most often of the radial artery, is a safe and simple procedure. With the exception of local pain, bruising and haematoma, clinically significant complications are rare [ 23 , 24 ]. Local pain may be decreased by local anaesthetic infiltration or the application of ice prior to the puncture [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike intensive care patients, these patients normally do not routinely have an arterial catheter in place, meaning that blood samples must be taken via an arterial puncture. However, arterial punctures can be painful, are associated with an increased risk of side effects such as haematoma and are often not readily available in many hospital departments [10], [11], [12]. No previous studies have investigated the benefit of using blood gas data to calibrate the ODC, and subsequently whether adequate precision can be achieved by ALPE using default blood gas parameters.…”
Section: Introductionmentioning
confidence: 96%
“…Peripheral arterial blood gas (ABG) sampling provides accurate assessment of pH, partial pressure of carbon dioxide (pCO 2 ), partial pressure of oxygen (pO 2 ) and bicarbonate (HCO 3 ). It is a safe and useful intervention both to assess and differentiate respiratory and metabolic acid–base abnormalities. Previous studies have suggested the utility of peripheral venous blood gas (VBG) analysis as a surrogate for arterial pCO 2 and pH in the assessment of patients at risk of ventilatory failure, stating advantages in patient comfort and risk without reducing clinical utility .…”
Section: Introductionmentioning
confidence: 99%